Pengaturan dan penggunaan sarana prasarana di SMPIT Insantama Leuwiliang Bogor - Wafiroh, Fifih; Agus Ali (Program Studi Manajemen Pendidikan Islam, 2024)
This article discusses the arrangement and procurement of infrastructure facilities at Insantama Leuwiliang Bogor. There are three activities carried out in the process of arranging infrastructure facilities, namely inventory, storage and maintenance, while the use of infrastructure facilities is a process that includes aspects of use where there are two principles that must be considered in the use of educational equipment, namely the principle of effectiveness and the principle of efficiency. The research method used in this study is a qualitative descriptive analysis method. This research was conducted using interview and observation techniques carried out at SMPIT Insantama. The results in this study are that arrangements have been made with competent people, providing coding for each item, storage is appropriate, maintenance continues to be carried out by the respective person in charge and there is a procedure for using infrastructure facilities which is the utilization of infrastructure facilities.